Avaliação genotóxica dos resíduos líquidos gerados nos equipamentos automatizados das análises hematológicas - Reynaldo, Eliana Mara Fortunato de Lucena (2009)
The inadequate disposal of liquid waste produced by clinical analysis laboratories may cause serious damages to the environment. The equipments that perform hematological exams use chemical substances such as cyanide, dimethylurea and formic acid, besides patients' blood samples. Moreover, besides the chemical reagents toxicity, there is the possibility of biological contamination, through contaminated blood. Inadequate procedures and lack of knowledge by area professionals contribute to make the situation worse. This work evaluated, using a questionnaire/interview in laboratory professionals in the city of Curitiba, the knowledge and degree of consciousness regarding the environmental problems that the wastes represent. In Curitiba, an average of 6300 exams are performed daily, generating a waste disposal of 430 liters, from which 67% are eliminated directly through the sanitary waste disposal. The waste solution toxicity from the two main equipments were evaluated through micronucleus genotoxical test and comet assay performed in fishes from the species Oreochromis niloticus exposed for 24 hours in aquariums containing the waste disposal solution. The wastes disposal from Maxm, Coulter and Celldyn 1400 from Abbott equipments were obtained in two different situations, with or without blood samples. In the experimental condition performed, no ecotoxicological damages were observed in the micronucleus test with the Maxm equipment waste with blood or in the comet assay in none of the conditions. Nevertheless, the wastes from the Celldyn equipment, independently of the situation and from the Maxm equipment without blood, cause damage induction. The biological contamination was investigated analyzing the presence of Hepatitis B virus by the Polymerase Chain Reaction (PCR) technique; yet the presence of this virus was not observed in the waste. The results indicate generation of a great volume of equipment waste, absence of treatment and consciousness and possibility of environmental damage. To minimize the problem, several actions, involving laboratories, manufactures, environmental and legislative organs are suggested.